2007
DOI: 10.1097/ta.0b013e31802d9700
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure From Diagnostic Imaging in Severely Injured Trauma Patients

Abstract: Trauma patients are exposed to significant radiation doses from diagnostic imaging, resulting in a small but measurable excess cancer risk. This small individual risk may become a greater public health issue as more CT examinations are performed. Unnecessary CT scans should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(99 citation statements)
references
References 26 publications
1
94
0
2
Order By: Relevance
“…Although there are no Brazilian data on the subject, it is estimated that, in the United States, between 1.5 and 2% of all diagnosed neoplasms are related to hospital radiation use 5 . Such data is relevant to this discussion, since full-body CT scans generate a radiation dose of 10-30mSv 6,8,[11][12][13][14][15] , which is up to 1,000 times greater than that of a PA chest X-ray, whose estimated dose is 0.01mSv 16 . Thus, a study which can demonstrate the safety of conventional tests, compared to full-body CT scans, can contribute greatly in improving the logistics of referrals to large Brazilian trauma centers 17,18 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…Although there are no Brazilian data on the subject, it is estimated that, in the United States, between 1.5 and 2% of all diagnosed neoplasms are related to hospital radiation use 5 . Such data is relevant to this discussion, since full-body CT scans generate a radiation dose of 10-30mSv 6,8,[11][12][13][14][15] , which is up to 1,000 times greater than that of a PA chest X-ray, whose estimated dose is 0.01mSv 16 . Thus, a study which can demonstrate the safety of conventional tests, compared to full-body CT scans, can contribute greatly in improving the logistics of referrals to large Brazilian trauma centers 17,18 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…Although the panscan protocol in trauma patients reduces mortality, radiation exposure must be considered. (17)(18)(19) On the other hand, some investigators have reported that whole body CT did not decrease mortality but did increase radiation exposure. (18,20) In this study, the average estimated effective dose from each type of CT was within the level of the typical effective dose in the AAPM report 96.…”
Section: Discussionmentioning
confidence: 99%
“…While ultrasonography, MRCP and endoscopic ultra sonography have the benefit of avoiding the delivery of ionizing radiation to patients, CT and the fluoroscopy associated with ERCP and IOC carry potential stochastic risks. Given the explosion in CT scanner use and indications 1,7,[18][19][20][21][22][23][24][25][26][27][28] (3 million CTs performed in 1980 v. 62 million in 2006), 8 radiation exposure is always a public health concern. This is evident in the nearly 6-fold increase in the per capita radiation exposure delivered from medical imaging.…”
Section: Discussionmentioning
confidence: 99%
“…39 The lifetime risk of cancer from all other causes is 42 in 100, and the risk of dying from a motor vehicle crash in the United States is 1 in 77. 28,[40][41][42] conclusion In summary, despite an increasing overall volume of admissions for pancreatic diseases, the frequency of inpatient CT imaging is decreasing while the use of MRCP/MRI is increasing. This observation is notable in the context of potential patient and physician concerns regarding the stochastic risks of ionizing radiation.…”
Section: Limitationsmentioning
confidence: 99%